2001
DOI: 10.1081/jas-100107547
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Bronchoconstriction in Elderly Asthmatics

Abstract: The impaired perception of bronchoconstriction in asthmatic patients may increase the risk of severe exacerbation. To characterize the perception of bronchoconstriction in elderly asthma patients, we compared the perception in older patients with that of younger patients. To determine the influence of perception of long-standing diseases, we further evaluated the perception in early-onset elderly asthma patients and in late-onset elderly asthma patients. The study group consisted of 80 stable asthmatic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
4
26
0
2
Order By: Relevance
“…Moreover, although age was not a significant predictor of Borg scale ratings in our regression analyses, we cannot say whether older age might lead to different results, because we examined a rather young sample. Since other studies have reported an influence of older age on the perception of dyspnea [41, 42], future studies comparing different age cohorts are clearly needed to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although age was not a significant predictor of Borg scale ratings in our regression analyses, we cannot say whether older age might lead to different results, because we examined a rather young sample. Since other studies have reported an influence of older age on the perception of dyspnea [41, 42], future studies comparing different age cohorts are clearly needed to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in this age group may not perceive respiratory decrements to the extent that younger individuals do. 15 Con- versely, older farmers who highly value the ability to continue farming regardless of health impairments 5 may disregard or underreport perceived symptoms that may be a harbinger of the end of field work. Whatever the reason, subjective reports of respiratory symptoms may not adequately characterize current health status.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Elderly patients with longstanding disease may have more severe airway obstruction than new-onset asthmatics but they complain less of dyspnea or wheeze. [13][14][15] Spirometry is considered a reliable and useful screening measure in older populations, [13][14][15] and an FEV 1 of 80% or less of predicted values can be used as an indicator of risk for obstructive disease in the elderly. 16,17 Symptoms which might point to asthma or obstructive disease in older adults includes nocturnal-associated breathlessness, dyspnea on exertion, rhinosinusitis, hay fever, daytime sleepiness, bronchitis, chest tightness, cough, atopic dermatitis, and wheeze.…”
mentioning
confidence: 99%
“…Dieser Faktor mag dazu beitragen, dass ältere Patienten die Schwere der Erkrankung oftmals unterschätzen. Bei Untersuchungen über die Wahrnehmung von Obstruktion verglichen Ekici et al [12] verschiedene Altersgruppen von Asthmatikern (<60 vs. >60 Jahre). Zusätzlich wurde geprüft, ob die Fä-higkeit zur Obstruktionswahrnehmung mit der Erkrankungsdauer korreliert.…”
Section: Gestörte Symptomwahrnehmungunclassified
“…Die Art und Weise, wie Patienten ihre Asthmasymptome (etwa Atemprobleme, nächt-liches Husten, Atemgeräusche) wahrnehmen und interpretieren, ist entscheidend dafür, wie sie ihrem Arzt gegenüber die Intensität der Symptome schildern und sich im Alltag verhalten. Beispielsweise werden Symptome einer sich verschlechternden Atemwegssituation, wie etwa Atemgeräusche, Giemen ("wheezing"), von älteren Patienten im Vergleich zu jüngeren häufig nicht oder nicht angemessen wahrgenommen [19], unterschätzt oder als Alterserscheinung interpretiert [12]. Notwendige medikamentöse und nicht-medikamentöse Maßnahmen werden so vom Patienten nicht oder zu spät eingeleitet.…”
Section: Diagnostik Und Asthmamanagementunclassified